‘Intelligent’ lockdown, intelligent effects? Results from a survey on gender (in)equality in paid work, the division of childcare and household work, and quality of life among parents in the Netherlands during the Covid-19 lockdown - Yerkes, Mara A.; André, Stéfanie C. H.; Besamusca, Janna W.; Kruyen, Peter M.; Remery, Chantal L. H. S.; van der Zwan, Roos; Beckers, Debby G. J.; Geurts, Sabine A. E. (PloS one, 2020)
The COVID-19 pandemic is more than a public health crisis. Lockdown measures have substantial societal effects, including a significant impact on parents with (young) children. Given the existence of persistent gender inequality prior to the pandemic, particularly among parents, it is crucial to study the societal impact of COVID-19 from a gender perspective. The objective of this paper is to use representative survey data gathered among Dutch parents in April 2020 to explore differences between mothers and fathers in three areas: paid work, the division of childcare and household tasks, and three dimensions of quality of life (leisure, work-life balance, relationship dynamics). Additionally, we explore whether changes take place in these dimensions by comparing the situation prior to the lockdown with the situation during the lockdown. We use descriptive methods (crosstabulations) supported by multivariate modelling (linear regression modelling for continuous outcomes; linear probability modelling (LPM) for binary outcomes (0/1 outcomes); and multinomial logits for multinomial outcomes) in a cross-sectional survey design. Results show that the way in which parents were impacted by the COVID-19 pandemic reflects a complex gendered reality. Mothers work in essential occupations more often than fathers, report more adjustments of the times at which they work, and experience both more and less work pressure in comparison to before the lockdown. Moreover, mothers continue to do more childcare and household work than fathers, but some fathers report taking on greater shares of childcare and housework during the lockdown in comparison to before. Mothers also report a larger decline in leisure time than fathers. We find no gender differences in the propensity to work from home, in perceived work-life balance, or in relationship dynamics. In conclusion, we find that gender inequality in paid work, the division of childcare and household work, and the quality of life are evident during the first lockdown period. Specifically, we find evidence of an increase in gender inequality in relation to paid work and quality of life when comparing the situation prior to and during the lockdown, as well as a decrease in gender inequality in the division of childcare and household work. We conclude that the unique situation created by restrictive lockdown measures magnifies some gender inequalities while lessening others. The insights we provide offer key comparative evidence based on a representative, probability-based sample for understanding the broader impact of lockdown measures as we move forward in the COVID-19 pandemic. One of the limitations in this study is the cross-sectional design. Further study, in the form of a longitudinal design, will be crucial in investigating the long-term impact of the COVID-19 pandemic on gender inequality.